MODERN CONCEPT OF DIGITAL IDENTIFICATION OF AIR PASSENGERS - N. M. Tyukalova; A. A. Razuvakin (Научный вестник МГТУ ГА)
The article presents the main provisions of the digital passenger identification concept based on the use of blockchain technology. It is summarized that the introduction of secure biometric identification of passengers at the airport will reduce the time and financial costs associated with the inspection and going through the passport and customs control. The problematic aspects of the current legislation of the Russian Federation regulating the application of this technology are analyzed. The technology Smart Path, developed by SITA is considered. The essence of this technology is the use of biometric data as a single identification taken at each stage of the journey. The possibilities of using blockchain technology as the basis of passenger identification before the departure are analyzed, while the blockchain technology eliminates the need for centralized processing and storage of personal data of air passengers. A computer science dealing with the chain of blocks based on the cryptosystem ensures the confidentiality of data and the absence of the possibility of information leakage or misuse. It is specially noted that the technology of cryptographic protection of air passengers biometric data will become an obstacle to using personal information for illegal purposes, and the capabilities of blockchain technology will allow cross-border data exchange during international flights. It is concluded that with the use of this technology, there will be no need to maintain the staff of workers responsible for document verification and control over the identification of passengers. All these functions will be replaced by a distributed database, which cannot be destroyed or hacked. On the basis of the study, it is proposed to amend the current legislation regulating the procedure for collecting and processing the personal data of airline passengers.